2018
DOI: 10.1186/s13104-018-3187-y
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of a Thai version internet addiction test

Abstract: ObjectiveThe aim was to assess the reliability and validity of a Thai version internet addiction test.ResultsCronbach’s alpha for the Thai version of the internet addiction test was 0.89. A three-factor model showed the best fit with the data for the whole sample, whereas the hypothesized six-factor model, as well as a unidimensional model of the internet addiction test, failed to demonstrate acceptable fit with the data. Three factors, namely functional impairment, withdrawal symptoms and loss of control, exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 39 publications
1
24
0
2
Order By: Relevance
“…This result is in accordance with the findings of a previous study in which the items contained in the neglect of duty domain in the study were also included underperformance problems, neglecting work, and personal activities disorder [17,22,23]. Interestingly, this domain can also be combined with time management, relationship problems, and social problems [12][13][14]16,17]. The third domain in the study is loss of control and the items included in it belonged to the performance problems, relationship problems, and withdrawal symptoms domains in studies in other countries [16,17].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This result is in accordance with the findings of a previous study in which the items contained in the neglect of duty domain in the study were also included underperformance problems, neglecting work, and personal activities disorder [17,22,23]. Interestingly, this domain can also be combined with time management, relationship problems, and social problems [12][13][14]16,17]. The third domain in the study is loss of control and the items included in it belonged to the performance problems, relationship problems, and withdrawal symptoms domains in studies in other countries [16,17].…”
Section: Discussionsupporting
confidence: 92%
“…Our analysis revealed that three-dimensional IAT displays better psychometric properties than the one-factor model. Prior studies indicated that several IAT models are one-factor to six-factor models [8][9][10][11][12][13][14][15][16][17]. The variability of the models could be due to diversity in the subjects' characteristics and cultural backgrounds [9,11,13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The level of addiction is categorized by non-internet addiction (0-30), mild (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49), moderate and severe internet addiction (80-100). The Thai version of IAT showed an excellent reliability of Cronbach's alpha of 0.85 [36] .…”
Section: Iatmentioning
confidence: 99%